TINGKAT KERUSAKAN SEL DARAH MERAH LELE DUMBO (Clarias gariepinus) YANG DIPAPARKAN DALAM ENDOSULFAN PADA KONSENTRASI SUBLETAL - Indra Gumay Yudha (Jurnal Perikanan Universitas Gadjah Mada, 2006)
The objective of this experiment was to study the effect of endosulfan on red blood cells of catfish, C. gariepinus. Ten fishes, (2-3 g of body weight), were kept in 30 l fish tank. Fish were exposed to 5 concentrations of endosulfan (1.71 ppb, 3.43 ppb, 5.14 ppb, 6.85 ppb and 8.57 ppb) for 6 weeks. The experiment was done in triplicates. The result showed that endosulfan caused the red blood cells damage by forming cerroids and lipofuscin complex. This impairment was over 90% of total red blood cells when fishes were exposured to endosulfan at 6.85-8.57 ppb.